The FloR master regulator controls flotation, virulence and antibiotic production in Serratia sp. ATCC 39006 - Yanes, Alex Quintero; Lee, Chin Mei; Monson, Rita; Salmond, George (Blackwell Publishing Ltd, 2020)
Serratia sp. ATCC 39006 produces intracellular gas vesicles to enable upward flotation in water columns. It also uses flagellar rotation to swim through liquid and swarm across semi-solid surfaces. Flotation and motility can be co-regulated with production of a β-lactam antibiotic (carbapenem carboxylate) and a linear tripyrrole red antibiotic, prodigiosin. Production of gas vesicles, carbapenem and prodigiosin antibiotics, and motility are controlled by master transcriptional and post-transcriptional regulators, including the SmaI/SmaR-based quorum sensing system and the mRNA binding protein, RsmA. Recently, the ribose operon repressor, RbsR, was also defined as a pleiotropic regulator of flotation and virulence factor elaboration in this strain. Here, we report the discovery of a new global regulator (FloR; a DeoR family transcription factor) that modulates flotation through control of gas vesicle morphogenesis. The floR mutation is highly pleiotropic, down-regulating production of gas vesicles, carbapenem and prodigiosin antibiotics, and infection in Caenorhabditis elegans, but up-regulating flagellar motility. Detailed proteomic analysis using TMT peptide labelling and LC–MS/MS revealed that FloR is a physiological master regulator that operates through subordinate pleiotropic regulators including Rap, RpoS, RsmA, PigU, PstS and PigT.